Containers in OpenStack : leverage OpenStack services to make the most of Docker, Kubernetes and Mesos - Singh, Pradeep Kumar; Kumari, Madhuri (Birmingham, UK : Packt Publishing, 2017)
A practical book which will help the readers understand how the container ecosystem and OpenStack work together. About This Book Gets you acquainted with containerization in private cloud Learn to effectively manage and secure your containers in OpenStack Practical use cases on container deployment and management using OpenStack components Who This Book Is For This book is targeted towards cloud engineers, system administrators, or anyone from the production team who works on OpenStack cloud. This book act as an end to end guide for anyone who wants to start using the concept of containerization on private cloud. Some basic knowledge of Docker and Kubernetes will help. What You Will Learn Understand the role of containers in the OpenStack ecosystem Learn about containers and different types of container runtimes tools. Understand containerization in OpenStack with respect to the deployment framework, platform services, application deployment, and security Get skilled in using OpenStack to run your applications inside containers Explore the best practices of using containers in OpenStack. In Detail Containers are one of the most talked about technologies of recent times. They have become increasingly popular as they are changing the way we develop, deploy, and run software applications. OpenStack gets tremendous traction as it is used by many organizations across the globe and as containers gain in popularity and become complex, it's necessary for OpenStack to provide various infrastructure resources for containers, such as compute, network, and storage. Containers in OpenStack answers the question, how can OpenStack keep ahead of the increasing challenges of container technology? You will start by getting familiar with container and OpenStack basics, so that you understand how the container ecosystem and OpenStack work together. To understand networking, managing application services and deployment tools, the book has dedicated chapters for different OpenStack projects: Magnum, Zun, Kuryr, Murano, and Kolla. Towards the end, you will be introduced to some best practices to secure your containers and COE on OpenStack, with an overview of using each OpenStack projects for different use cases. Style and approach An end to end guide for anyone who wants to start using the concept of containerization on private cloud.
Providing containerized images of neutron plugins -- Nesting VMs and Magnum use cases -- Installation of Kuryr -- Walk-through -- Summary -- Chapter 8: Murano -- Containerized Application Deployment on OpenStack -- Introduction to Murano -- Murano concepts -- Environment -- Package -- Session -- The environment template -- Deployments -- Bundle -- Categories -- Key features -- Production-ready applications -- Application catalog UI -- Distributing workloads -- Application development -- Murano repository -- Cinder volumes -- Barbican support -- HOT packages -- Murano components -- The Murano API -- The Murano engine -- The Murano agent -- The Murano dashboard -- Walk-through -- Murano DevStack installation -- Deploying a containerized application -- Summary -- Chapter 9: Kolla -- Containerized Deployment of OpenStack -- Kolla introduction -- Key features -- Highly available deployment -- Ceph support -- Image building -- Docker hub support -- Local registry support -- Multiple build sources -- Dockerfile customization -- Architecture -- Deploying containerized OpenStack services -- Setting up a local registry -- Automatic host bootstrap -- Building images -- Deploying images -- Summary -- Chapter 10: Best Practices for Containers and OpenStack -- The advantages of different OpenStack projects -- Best practices for securing and deploying containers -- Summary -- Index.
Online resource; title from title page (Safari, viewed February 1, 2018).
eBooks on EBSCOhost
Keywords: Cloud computing; Information technology -- Management; Application software -- Development; Open source software; Infonuagique; Technologie de l'information -- Gestion; Logiciels d'application -- Développement.; Logiciels libres; Computer networking & communications; Computer architecture & logic design; Cloud computing; Computers -- Systems Architecture -- General; Computers -- System Administration -- General; Application software -- Development; Cloud computing; Information technology -- Management; Open source software